2008
DOI: 10.1159/000151710
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Pulmonary Thromboembolism by Neutrophil Elastase in Collagen-Induced Arthritis Mice and Effect of Recombinant Human Soluble Thrombomodulin

Abstract: We previously reported that during total knee arthroplasty in rheumatoid arthritis (RA) patients, the use of tourniquet might promote local release of neutrophil elastase (NE) from neutrophils, which may contribute to the development of pulmonary thromboembolism (PTE) and tissue injury. The aim of this study was to develop PTE by the use of NE in a mouse model of collagen-induced arthritis (CIA) and investigate the relationship between thrombus and endothelial cells as well as the effect of recombinant human s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 67 publications
1
6
0
Order By: Relevance
“…We found prolonged tourniquet and operating times for MIS TKAs, which is in agreement with other publications [11,24,25,27,37]. Therefore, we assume that the published risks and disadvantages of a tourniquet [3,28,34,42,43] could be more pronounced for MIS TKA.…”
Section: Discussionsupporting
confidence: 91%
“…We found prolonged tourniquet and operating times for MIS TKAs, which is in agreement with other publications [11,24,25,27,37]. Therefore, we assume that the published risks and disadvantages of a tourniquet [3,28,34,42,43] could be more pronounced for MIS TKA.…”
Section: Discussionsupporting
confidence: 91%
“…Although pulmonary complications commonly occur in RA patients, involvement of the lungs in animal models of RA is poorly documented. One report [9] described increased numbers of cells in BALFs in DBA/1 mice with CIA, whereas another study [12] failed to show any histopathological lung abnormality. In the present study of CIA in DBA/1 mice, we found that, in addition to their joint lesions, the animals also showed a variable degree of pulmonary involvement.…”
Section: Discussionmentioning
confidence: 99%
“…The pleura and the airways, as well as the interstitium and vasculature of the lung can be affected . Pleuritis is the most common manifestation of lung disease associated with RA, but this condition often remains asymptomatic . Rheumatoid arthritis‐interstitial lung disease ( RA ‐ ILD ) refers to a diverse range of pulmonary disorders that affect the interstitium of the lung.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations